Certain problematic aspects of the criminalization of domestic violence - Zamakhin, A. (НДІ ПЗІР НАПрН України, 2023)
The article focuses on analyzing the normative legal framework and judicial practice in Ukraine concerning the criminalization of domestic violence, with a particular emphasis on the provisions of Article 1261 of the Ukrainian Criminal Code. The author thoroughly examines the historical context and international obligations, including the Istanbul Convention, which have prompted the reform of relevant legislation. The article assesses the importance of the legal qualification of economic violence, its role in the structure of domestic violence, and the specifics of its legal application. It highlights the problems of existing legislative norms, identifying shortcomings and contradictions that arise in their application. Considerable attention is paid to the analysis of judicial practice, illustrating the variety of approaches to applying Article 1261 of the Ukrainian Criminal Code and determining the systematic nature of domestic violence. Special attention is given to the systematic nature of domestic violence as a key criterion in defining this crime, as well as its legal understanding and interpretation. The analysis of scientific literature and judicial practice allows stating that the systematic nature of domestic violence is characterized by two indicators: quantitative, meaning the multiplicity of periodically committed acts, and qualitative, meaning the interconnection and internal unity that form a certain line of behavior of the offender towards a specific victim or victims. Only with the presence of both quantitative and qualitative criteria can it be asserted that the violence is systematic. The article makes an important contribution to understanding the issues of domestic violence in Ukraine, highlighting both theoretical and practical aspects of this issue. The author provides substantiated recommendations for improving legislation, particularly through amendments to current norms, to adequately reflect the complexity and multifaceted nature of this social problem. The necessity of developing comprehensive strategies to counter domestic violence, including both legal and socio-educational aspects, is also emphasized. Стаття зосереджується на аналізі нормативно-правової бази та судової практики в Україні, що стосуються криміналізації домашнього насильства, з особливим акцентом на положеннях ст. 1261 Кримінального кодексу України. Автор детально розглядає історичний контекст та міжнародні зобов›язання, включаючи Стамбульську конвенцію, які спонукали до реформування відповідного законодавства. У статті аналізується важливість правової кваліфікації економічного насильства, його місце у структурі домашнього насильства та специфіка правозастосування. Висвітлюються проблеми існуючих законодавчих норм, виявлені недоліки та суперечності, які виникають у процесі їх застосування. Значна увага приділяється аналізу судової практики, що ілюструє різноманітність підходів до застосування ст. 1261 Кримінального кодексу України та визначення систематичності домашнього насильства. Особливу увагу приділено систематичності домашнього насильства як ключового критерію у визначенні цього злочину, а також його юридичному розумінню та тлумаченню. Аналіз наукової літератури й судової практики дає можливість зазначити, що систематичність домашнього насильства характеризується двома показниками: кількісним, тобто багаторазовістю періодично здійснюваних дій, і якісним, тобто взаємозв’язком, внутрішньою єдністю, що утворюють певну лінію поведінки винного щодо конкретного потерпілого чи потерпілих. Лише за наявності як кількісного, так і якісного критерію можна стверджувати, що насильство має систематичний характер. Стаття представляє важливий внесок у розуміння проблематики домашнього насильства в Україні, висвітлюючи як теоретичні, так і практичні аспекти цього питання. Автор надає обґрунтовані рекомендації щодо вдосконалення законодавства, зокрема через внесення змін до чинних норм, аби адекватно відображати складність та многогранність цієї соціальної проблеми. Також увага акцентується на необхідності розробки комплексних стратегій протидії домашньому насильству, що включають як правові, так і соціально-освітні аспекти.
Keywords: criminal offense; domestic violence; economic violence; psychological violence; systematic nature; кримінальне правопорушення; домашнє насильство; економічне насильство; психологічне насильство